2011
DOI: 10.5194/hess-15-1427-2011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing water resources adaptive capacity to climate change impacts in the Pacific Northwest Region of North America

Abstract: Abstract. Climate change impacts in Pacific Northwest Region of North America (PNW) are projected to include increasing temperatures and changes in the seasonality of precipitation (increasing precipitation in winter, decreasing precipitation in summer). Changes in precipitation are also spatially varying, with the northwestern parts of the region generally experiencing greater increases in cool season precipitation than the southeastern parts. These changes in climate are projected to cause loss of snowpack a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…SWE/P substantially decreases with each time period, indicating a hydrologic regime shift from a snow-rain-dominated to a rain-dominated basin. This is consistent with predictions in the Pacific Northwest [5,14,[64][65][66][67][68]. Vynee et al [65] predicted SWE to decrease more than 50% by the 2080s in the URB.…”
Section: Snow Water Equivalent and Precipitationsupporting
confidence: 88%
“…SWE/P substantially decreases with each time period, indicating a hydrologic regime shift from a snow-rain-dominated to a rain-dominated basin. This is consistent with predictions in the Pacific Northwest [5,14,[64][65][66][67][68]. Vynee et al [65] predicted SWE to decrease more than 50% by the 2080s in the URB.…”
Section: Snow Water Equivalent and Precipitationsupporting
confidence: 88%
“…A study by Wu et al [14] indicated that projected climate change will have great impacts on snow dominant streams, leading to lower summer streamflows and warmer summer stream temperature with smaller effects on transient and rain dominant regimes in the northwestern region of the United States. Hamlet [15] studied the projected impacts of climate change on seasonal rainfall in the Pacific Northwest region of North America and performed hydrologic simulations to support water resources management, flood control, hydropower development and other water related environmental services in the region. Thodsen [16] combined climate model generated precipitation and potential evapotranspiration and a hydrologic model to study the impact of climate change on six major Danish catchments and reported potential future increases in the 100-year and 1000-year precipitation leading to increases in discharge that are approximately twice as much.…”
Section: Introductionmentioning
confidence: 99%
“…Only through further coupling of the continental or biogeographic regions and parcel scales can we better understand the mechanisms behind the spatial patterns observed in this study. Indeed, multi-level water governance in the entire basin is needed to address the challenges of a changing environment caused by climate change (Hamlet, 2011). In future studies, we suggest that our analysis be linked with regional and parcel data to better evaluate the dynamics of water resource vulnerability in the CRB.…”
Section: Discussionmentioning
confidence: 99%